Reliability and Probability or the Birth of Probabilism - Nekrašas, Evaldas (Problemos, 1987)
An attempt is made to consider the birth of probabilistic philosophy of science, namely, the initial stage of its development (from Karneades until the beginning of the 20th century). It is shown how on the background of the classical opposition between reliable knowledge and probable opinion the idea of scientific knowledge shaped itself and strengthened. A variety of forms of manifestation of the idea in history is surveyed, and the factors, leading to the fall of the epistemological absolutism in the beginning of the 20th century, are examined.